2009
DOI: 10.1007/s10447-009-9084-2
|View full text |Cite
|
Sign up to set email alerts
|

Does Professional Suitability Matter? A National Survey of Australian Counselling Educators in Undergraduate and Post-Graduate Training Programs

Abstract: This Australian national study was undertaken to profile the unsuitable counselling student, and to achieve greater operational specificity to guide counselling educators who must make critical decisions that impact admittance to the counselling profession. Findings suggest that in every 25 students as many as three will have questionable suitability for counselling, evidenced primarily by problems associated with self awareness and interpersonal issues, areas of functioning that are rarely systematically or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…An exhaustive search of the literature failed to find any articles that examined doctoral-level training of counselor educators outside of the U.S. In Western non-U.S. countries, counselors are predominantly trained at the undergraduate and postgraduate level, with doctoral level training residing primarily within the field of counseling psychology (Brear and Dorrian 2010;British Association for Counseling and Psychotherapy 2011;Sharpley et al 2004;Stern 1985;Watts and Esbroeck 2000).…”
Section: Extant Literaturementioning
confidence: 98%
“…An exhaustive search of the literature failed to find any articles that examined doctoral-level training of counselor educators outside of the U.S. In Western non-U.S. countries, counselors are predominantly trained at the undergraduate and postgraduate level, with doctoral level training residing primarily within the field of counseling psychology (Brear and Dorrian 2010;British Association for Counseling and Psychotherapy 2011;Sharpley et al 2004;Stern 1985;Watts and Esbroeck 2000).…”
Section: Extant Literaturementioning
confidence: 98%
“…Reflection and local discussion have also highlighted that it is often easier to articulate suitability by its absence and studies have attempted to understand suitability by profiling the 'unsuitable' student (Brear and Dorrian 2010). The fact that HCPC guidance on health and good character focuses mainly on disciplinary issues and involvement in criminal or civil proceedings (HCPC 2012) provides some insight into why this may be the case.…”
Section: Opinionmentioning
confidence: 98%
“…The counselor trainees would unlikely observe modeling of working with difficult clients in their own personal counseling, unless possibly in a group therapy format. Braer and Dorrian (2010) suggested that only a small percent of counselor trainees (14.1-14.4%) were not fit because of difficult behaviors. Without the direct experience of working with a difficult client or acting as a difficult client, counselor trainees may assess themselves incorrectly in this area.…”
Section: Basic Clinical Skillsmentioning
confidence: 99%